2015
DOI: 10.1111/inr.12166
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review of experiences of patients with rheumatoid arthritis

Abstract: Establishing a positive healthcare professional-patient relationship is crucial and healthcare professionals are in a position to provide greater informational and emotional support to patients. Policy makers and healthcare organizations need to look into ways to enhance the healthcare services to better suit RA patients' needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The past decades have shown large improvements in disease activity control of inflammatory rheumatic diseases, as shown by the large decreases in the levels of physical disability, anxiety, and depression [17]. However, the quality of life of patients with inflammatory rheumatic diseases remains considerably lower than that in the general population [13] and is comparable to that in other chronic somatic diseases including cardiovascular conditions and diabetes [1]. Thus, many patients show some level of heightened psychological distress, with a substantial percentage developing clinically relevant levels of distress, such as depression and anxiety, with prevalence rates varying between 10% and 40% depending on the criteria and instruments used (e.g., clinical interviews show lower percentages than screening questionnaires) [7,8,17e19].…”
Section: Psychological Burden Of Inflammatory Rheumatic Diseasesmentioning
confidence: 99%
“…The past decades have shown large improvements in disease activity control of inflammatory rheumatic diseases, as shown by the large decreases in the levels of physical disability, anxiety, and depression [17]. However, the quality of life of patients with inflammatory rheumatic diseases remains considerably lower than that in the general population [13] and is comparable to that in other chronic somatic diseases including cardiovascular conditions and diabetes [1]. Thus, many patients show some level of heightened psychological distress, with a substantial percentage developing clinically relevant levels of distress, such as depression and anxiety, with prevalence rates varying between 10% and 40% depending on the criteria and instruments used (e.g., clinical interviews show lower percentages than screening questionnaires) [7,8,17e19].…”
Section: Psychological Burden Of Inflammatory Rheumatic Diseasesmentioning
confidence: 99%
“…It is important to explore patients’ experiences/perceptions on their RA and their resulting support needs to help optimize their illness experiences. Due to the fact that very limited qualitative studies have been conducted to explore patients’ experiences/perceptions of RA on Asian populations and none in Singapore (Poh, He, Lee, Cheung, & Chan, 2015), this study aims to fill in this gap.…”
Section: Introductionmentioning
confidence: 99%
“…In our research, some patients' lack of confidence in the therapy turned into abandonment or modification of treatment in several informants. The literature review by Poh et al (2015) also includes this aspect, along with frustration with the successive changes of medication and the extension of treatment to find an improvement. However, nurses can play an important role in educating patients about the principles of "treat to target" to enhance adherence, as has been demonstrated in different studies (van Eijk-Hustings et al, 2012;Zangi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies that correlate a poor body image with low self-esteem, quality of life, or functionality (Jorge, Brumini, Jones, & Natour, 2010;Lack, Noddings, & Hewlett, 2011;Williams, Nester, & Ravey, 2007). However, in this body of research, there is a lack of variety in study populations and types of health care services as has been pointed by Poh et al (2015) in an integrative review. They found that the majority of the reviewed studies had been conducted in Western countries and, as culture plays an important role in influencing patients' illness experiences and needs, self-management strategies may differ in other regions (Poh, He, Lee, Cheung, & Chan, 2015).…”
Section: Introductionmentioning
confidence: 99%